PENDAMPINGAN RINTISAN UMKM KERUPUK IKAN DI DESA SELETRENG KECAMATAN KAPONGAN KABUPATEN SITUBONDO - Hermawan, Angga Dimas; Hendrawan, Rizqi Ainur; Putri, Sari Rahmawati; Wulandari, Amelia Puspita; Sugiarto, Bambang; Saputra, Krisna Arga (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2023)
Seletreng Village, Kapongan District, Situbondo Regency has a coastal area geographically. The condition impacts to abundance of marine products, which gives rise to home-based businesses processing fishery products indirectly. The businesses are still home-based start-ups or are small-scale production. The existence of newly started small businesses or micro small and medium enterprises (MSMEs) certainly has several problems that require assistance and strengthening. Newly started MSME generally still does not have legality, the main raw materials are selected fish obtained in certain seasons, and lack of ability in branding and digital marketing aspects. The strengthening MSME is purposed to newly started MSME are able to compete and have quality through 1) Assistance MSME legality in the form of Business Identification Number, SPP-IRT, and Halal Certification, 2) Innovation in substitute raw materials, 3) Assistance and training in product branding and digital marketing. The service carried out in the UNEJ KKN Building Villages (UMD) program has an achievement target: MSME has received assistance, and strengthening can compete and has high quality. Sustainability is also a serious concern so MSME can continue to run in the market, so the service train business actors in operating marketplaces.